DEVELOPING PROBLEM BASED LEARNING (PBL)-ORIENTED PICTORIAL STORY MATERIALS ASSISTED BY ANDROID TO IMPROVE SCIENCE LEARNING OUTCOMES - Siti Zulifah; Murtono; Santoso (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aimed to develop a Problem Based Learning (PBL)-oriented pictorial story materials assisted by android to improve science learning outcomes at grade IV Elementary School. The approach used in this study was research and development (R&D) with mixed methods design. The subjects in this study were students at grade IV SDN 1 and 2 Manyargading, SDN 1 and 2 Bandungrejo, and SDN Teluk Kulon Kabupaten Jepara. Data were collected by using questionnaires, observations, interviews, and documentation. The PBL-oriented pictorial story materials assisted by android media were developed by referring to the stages of development proposed by Borg and Gall. The results showed that PBL-oriented pictorial story materials assisted by android were feasible to improve science learning outcomes. This was based on the results of the validity test, the effectiveness test, and the practicality test of the materials. The result of validity test revealed that the assessment from the material, media, and language experts as well as the practitioners was good. Then, the result of the effectiveness test indicated that students’ learning outcomes increased from an average pretest of 51.2 to 76.8 in the posttest. The result of main field testing found that the average score of the students’ learning outcomes in the experimental class was (86.5), which was better than the score in the control class (73.2). The result of paired-sample test showed that the value of p = 0.000 (p < 0.05), meaning that there were significant differences in the students’ learning outcomes in the experimental and control class. Thus, it was said that PBL-oriented pictorial story materials assisted by android were effective to improve science learning outcomes. Finally, the result of practicality test obtained that PBL-oriented pictorial story materials assisted by android received a good response from students and teachers.